The role of educational strategies in human development: an example of using Key Word Method in teaching Arabic as a second language in Malaysia - Yaakub, Muhamadul Bakir (David Publishing Company, 2010)
Abstract: This paper is an attempt to discover and recognize the important role of educational strategies in developing human capital in which they become positive agents of human society such as academic achievement, intellectual abilities, interpersonal skills and also self-esteem. These will be measured using a survey instrument that classifies learning performance via test scores, to test the hypothesis that learning a language will lead to comparable positive self-development, but undirected language learning affects academic achievement negatively. Therefore, Key-word methods in learning Arabic language will be used as directed Arabic language learning to measure the significant correlation to both academic and non-academic development of the learners in which the effectiveness of mnemonic strategy in vocabulary memorization is associated with the self-consciousness and personal psyches of the learners. Consequently, they appreciate the knowledge and values they gained from their learning activities, which help them to perform better than students who did not use this type of learning strategy in learning Arabic language. Teachers, on the other hand, would also able to observe the important impact of Arabic language learning on learners’ academic performance and personality development. Therefore, education is simply a process of acquiring a new knowledge in creating an environment in which students and teachers learn something for themselves.